An expert panel Delphi consensus statement on the use of palliative care in the management of patients with pulmonary arterial hypertension. (5th January 2022) - Wilson, Melisa; Anguiano, Rebekah H.; Awdish, Rana L. A.; Coons, James C.; Kimber, Amy; Morrison, Melissa; Paulus, Sara; Schmit, Ann; Spexarth, Frank; Swetz, Keith M.; Verlinden, Nathan J.; Whittenhall, Mary E.; et al.
Abstract: Mortality in pulmonary arterial hypertension (PAH) remains high and referral to palliative or supportive care (P/SC) specialist services is recommended when appropriate. However, access to P/SC is frequently a challenge for patients with a noncancer diagnosis and few patients living with PAH report P/SC involvement in their care. A modified Delphi process of three questionnaires completed by a multidisciplinary panel ( N = 15) was used to develop expert consensus statements regarding the use of P/SC to support patients with PAH. Panelists rated their agreement with each statement on a Likert scale. There was a strong consensus that patients should be referred to P/SC when disease symptoms become unmanageable or for end‐of‐life care. Services that achieved consensus were pain management techniques, end‐of‐life care, and psychosocial recommendations. Palliative or supportive care should be discussed with patients, preferably in‐person, when disease symptoms become unmanageable, when starting treatment, when treatment‐related adverse events occur or become refractory to initial intervention. Care partners and patient support groups were considered important in improving a patient's overall health outcomes, treatment adherence, and perception of care. Most patients with PAH experience cognitive and/or psychosocial changes and those who receive psychosocial management have better persistence and/or compliance with their treatment. These consensus statements provide guidance to healthcare providers on the "who and when" of referral to palliative care services, as well as the importance of focusing on the psychosocial aspects of patient care and quality of life.